Prosthetic valve endocarditis from Mycobacterium chimaera infection causing granulomatous interstitial nephritis. (2020) - Trautman, Christopher; Da Costa, Jonathan R.; Cortese, Cherise; Aslam, Nabeel
Abstract: Mycobacterium chimaera is a rare infection associated with cardiopulmonary bypass. We describe a case of granulomatous interstitial nephritis caused by M. chimaera in a patient with prosthetic aortic valve endocarditis. A 63-year-old female with a mechanical aortic valve replacement developed fatigue, 20 lbs. weight loss, anemia, and an elevated creatinine. Fat pad aspirate at an outside hospital was suspicious for amyloidosis which prompted hematology referral at our institution. Bone marrow biopsy revealed a single granuloma, negative for amyloid or acid fast bacillus (AFB). She was admitted to our hospital for worsening kidney function refractory to intravenous fluid challenge. Transesophageal echocardiogram showed aortic root abscess and valve vegetation with negative blood cultures at seven days. Renal biopsy showed granulomatous interstitial nephritis and negative AFB stain. Prednisone 40 mg was started and renal function partially improved. Blood cultures obtained before biopsy subsequently grew M. chimaera . Three-drug antimicrobial therapy was initiated and prednisone discontinued. One month later, creatinine improved and follow up echocardiogram showed no lesion. Our case highlights this rare infection inducing granulomatous interstitial nephritis despite lack of positive AFB or gram stains on renal biopsy.